Pendekatan Living Lab sebagai penerapan SDGs terhadap pertumbuhan ekonomi dan infrastruktur pada Kawasan Utama Kota Bandung - Pascalina, Donna (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The living lab approach provides solutions to solve cities at a small scale and in limited environments that are scalable and sustainable. One of the SDGs targets is economic growth and infrastructure. With the concept of a living lab approach on initiatives to increase economic growth and infrastructure, it can create a pilot area so that the implementation of these initiatives can be duplicated in other areas. The method used is PBRE (plan, build, run, evaluate). With this, the solutions implemented are not only implemented but also have a direct impact on the users (citizen). The implementation of SDGs in Goals 8 and 9, increasing inclusive and sustainable economic growth and building resilient infrastructure with MSME indi-cators to financial services and connectivity (internet access) are the foundations for implementing the SDGs with the Living Lab approach which will be discussed in this study.